Implementation of Women's Movement Values in Java as History Learning Resources - Az-Zahra, Aqilla (JURNAL HISTORICA, 2023)
The struggle of the women's movement in the Java region in obtaining rights and authorities which were initially opposed during the movement provided lessons for the community, especially students in history learning activities. The aim of the research is for students to take the value of the struggle from the women's movement as implementation in everyday life to advance education that has been built by women's movement figures during the period of the national movement. This research was conducted using a descriptive research type using a qualitative approach. Data collection techniques were carried out through literature studies by reviewing various sources ranging from articles, research-related literature, as well as analysis of movement discussions related to women. The value of the struggle of the Javanese women's movement can be implemented in history lessons by integrating Javanese women's movement material into the school curriculum and opening extracurriculars with the theme of the history of the Javanese women's movement. The struggle of the women's movement is expected to have a positive impact today such as gender empowerment, expansion of education, equal rights and authority or freedom and just leadership. Keywords: Value of struggle, Javanese Women's Movement, Education, Rights and authority, Learning History.